Analisis Ekonomi Keterkaitan Ekosistem Mangrove dengan Sumber Daya Udang - Osmaleli Osmaleli; Tridoyo Kusumastanto; Meti Ekayani (Journal of Agriculture, Resource and Environmental Economics, 2014)
Mangroves provide a wide range of ecosystem services. Therefore, the existence of mangrove ecosystem needs to be maintained ecologically, economically and socially. This study aimed to identify the mangrove ecosystem linkages with shrimp. Data used in this study were primary and secondary data to generalize a case study on shrimp and mangrove ecosystem linkages in Pabean Udik Village Indramayu regency. The economy analysis of the relationship between mangroves and shrimp used mathematical equations by Barbier and Ivar (1994). Mangrove ecosystem linkage with shrimp seen from the marginal productivity of mangrove area (MPM) was 153.454 tons per km2, while the marginal productivity of fishing effort (MPE) wais 0,305 tons per trip using the shrimp catching boat. The study showed that the decline in mangrove ecosystems area would affect the decline in shrimp production, and the increase in mangrove ecosystems area would affect the incrase in the number of shrimp production.